Altered bioenergetics and mitochondrial dysfunction of monocytes in patients with COVID‐19 pneumonia. Issue 12 (5th November 2020) - Gibellini, Lara; De Biasi, Sara; Paolini, Annamaria; Borella, Rebecca; Boraldi, Federica; Mattioli, Marco; Lo Tartaro, Domenico; Fidanza, Lucia; Caro‐Maldonado, Alfredo; Meschiari, Marianna; Iadisernia, Vittorio; Bacca, Erica; et al.
Abstract: In patients infected by SARS‐CoV‐2 who experience an exaggerated inflammation leading to pneumonia, monocytes likely play a major role but have received poor attention. Thus, we analyzed peripheral blood monocytes from patients with COVID‐19 pneumonia and found that these cells show signs of altered bioenergetics and mitochondrial dysfunction, had a reduced basal and maximal respiration, reduced spare respiratory capacity, and decreased proton leak. Basal extracellular acidification rate was also diminished, suggesting reduced capability to perform aerobic glycolysis. Although COVID‐19 monocytes had a reduced ability to perform oxidative burst, they were still capable of producing TNF and IFN‐γ in vitro . A significantly high amount of monocytes had depolarized mitochondria and abnormal mitochondrial ultrastructure. A redistribution of monocyte subsets, with a significant expansion of intermediate/pro‐inflammatory cells, and high amounts of immature monocytes were found, along with a concomitant compression of classical monocytes, and an increased expression of inhibitory checkpoints like PD‐1/PD‐L1. High plasma levels of several inflammatory cytokines and chemokines, including GM‐CSF, IL‐18, CCL2, CXCL10, and osteopontin, finally confirm the importance of monocytes in COVID‐19 immunopathogenesis. SYNOPSIS: Investigation of patients with COVID‐19 pneumonia revealed that SARS‐CoV‐2 infection affects innate immunity by reshaping peripheral blood monocyte subsets and altering their functionality, in terms of bioenergetics, membrane potential and expression of checkpoint inhibitors. A peripheral blood increase in intermediate monocytes, reduction of classical monocytes, increase of circulating immature monocytes and upregulation of PD‐1 and PD‐L1 on such cells characterize patients with COVID‐19 pneumonia. Monocytes display reduced oxidative phosphorylation, reduced extracellular acidification rate and altered mitochondrial ultrastructure. Monocytes had a reduced capability to perform the respiratory burst, although they still remain able to produce inflammatory cytokines. Several inflammatory cytokines and chemokine, including GM‐CSF, IL‐18, CCL2, IL‐6, CXCL10 and osteopontin are present at high concentration in plasma from COVID‐19 patients. Abstract : Investigation of patients with COVID‐19 pneumonia revealed that SARS‐CoV‐2 infection affects innate immunity by reshaping peripheral blood monocyte subsets and altering their functionality, in terms of bioenergetics, membrane potential and expression of checkpoint inhibitors.